Tumor suppressive miR-99b-5p as an epigenomic regulator mediating mTOR/AR/SMARCD1 signaling axis in aggressive prostate cancer - Waseem, Mohammad; Gujrati, Himali; Wang, Bi-Dar (Frontiers in Oncology, 2023)
African American (AA) men exhibited 2.3-fold higher PCa incidence and 1.7-fold higher PCa mortality rates when compared to the European American (EA) men. Besides the socioeconomic factors, emerging evidence has highlighted that biological risk factors may play critical roles in the AA PCa disparities. Previously, we have shown that downregulated miR-99b-5p and upregulated mTOR cooperatively promotes the AA PCa aggressiveness and drug resistance. In this study, we aimed to explore the miR-99b-5p/mTOR/AR/SMARCD1 signaling axis in AA PCa aggressiveness. Specifically, the immunofluorescence staining and western blot analysis have revealed that nuclear mTOR, AR, and SMARCD1 were highly expressed in AA PCa (MDA PCa 2b) compared to EA PCa (LNCaP) cell line. Western blot analysis further revealed that miR-99b-5p inhibited protein levels of mTOR, AR/AR-V7 and SMARCD1 in cytoplasm and nuclei of EA and AA PCa. The in-vitro functional (MTT, TUNEL, and clonogenic) assays have demonstrated that miR-99b-5p effectively inhibited cell proliferation/survival and induced cell apoptosis in EA and AA PCa cells. Moreover, combination of miR-99b-5p and enzalutamide (Enz) synergistically enhances the cytotoxicity against aggressive AA PCa and castrationresistant prostate cancer (CRPC). mTOR ChIP-qPCR assays further demonstrated that miR-99b-5p or miR-99b-5p/Enz significantly reduces the recruitment of mTOR to the genes involved in the metabolic reprogramming in CRPC. Taken together, miR-99b-5p may function as an epigenomic driver to modulate the mTOR/AR/SMARCD1 signaling axis in AA PCa and resistant CRPC.